What is the prognostic value of lymph node yield on the outcomes of patients with oral cavity squamous cell carcinoma?. Issue 28 (1st October 2022) - Khalil, Carlos; Khoury, Mark; Fu, Rui; Enepekides, Danny; Higgins, Kevin; Karam, Irene; Bayley, Andrew; Poon, Ian; Truong, Tra; Husain, Zain Ali; Eskander, Antoine
Abstract : 330 Background: Lymph node metastases are associated with poor prognosis in oral cavity squamous cell carcinoma (OCSCC). In colorectal, lung, and gastric cancers, the number of lymph nodes removed during primary surgery, lymph node yield (LNY), is an established quality indicator that links with patient survival. As such, clinical guidelines have included a minimum (18) number of nodes to be resected, despite a lack of statistical evidence that supports such a LNY threshold. Currently, this kind of recommendation does not exist for OCSCC. Here, we used a novel single-centre dataset to evaluate the prognostic capacity of LNY on regional failure, locoregional recurrence and disease-free survival (DFS) in patients with OCSCC treated by primary neck surgery. Methods: This retrospective cohort study took place at Sunnybrook Hospital in Toronto, Canada and involved chart review data of all adult patients with treatment-naive OCSCC undergoing primary neck dissection. For each outcome, we first used the maximally selected rank statistics and a bias-corrected C-index to identify an optimal threshold of LNY, and then used a multivariable Cox proportional hazards model to assess the association between high LNY (> threshold) and each outcome. Results: Among the 579 OCSCC patients receiving primary neck dissection, 61.7% (n = 357) were male with mean age of 62.9 years (SD: 13.1) at cancer diagnosis. When adjusting for sociodemographic and clinical factors, LNY > 15 was significantly associated with improved DFS (adjusted HR [aHR]: 0.73, 95% CI: 0.54-0.98) and locoregional control (aHR: 0.68, 95% CI: 0.49-0.95), while LNY > 11 was associated with better regional control (aHR: 0.45, 95% CI: 0.26-0.76). Conclusions: Our study findings suggested high LNY to be a strong independent predictor of various patient-level quality of surgical care metrics. The optimal LNY we found (15 or 11) was lower than the conventionally recommended (18), which calls for further research to establish the validity in practice.